The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.2139/ssrn.1018345
|View full text |Cite
|
Sign up to set email alerts
|

The Policy Determinants of Investment in Tertiary Education

Abstract: for their comments and input during the preparation of the study. The collaboration and the expertise of Paulo Santiago and Thomas Wecko were also particularly useful, as well as comments we received from other colleagues of the OECD Directorate for Education. The comments of Paul Swain and Sven Blondal were particular useful to prepare the final version of this article. The views expressed here are those of the authors and do not necessarily represent those of the OECD or its member countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
42
0
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(43 citation statements)
references
References 25 publications
0
42
0
1
Order By: Relevance
“…and the opportunity costs, in terms of foregone labour market earnings, associated with participation in tertiary education. Oliveira Martins et al (2009) show that higher internal rates of return -as estimated by Boarini and Strauss (2010) -lead to higher graduation rates in a panel of 20 OECD countries.…”
Section: Demand For Tertiary Educationmentioning
confidence: 96%
See 2 more Smart Citations
“…and the opportunity costs, in terms of foregone labour market earnings, associated with participation in tertiary education. Oliveira Martins et al (2009) show that higher internal rates of return -as estimated by Boarini and Strauss (2010) -lead to higher graduation rates in a panel of 20 OECD countries.…”
Section: Demand For Tertiary Educationmentioning
confidence: 96%
“…Demand for tertiary education entails both monetary and non-monetary returns. As discussed in Oliveira Martins et al (2009), the monetary returns of tertiary education (compared with an upper secondary degree) can be summarized by the internal rate of return to investment in tertiary education. This return is a function of the expected benefits of graduating --which include net wage increases, higher employment probabilities, higher statutory pension benefits and higher productivity levels due to delayed entry and exit into the labour market (given rising overall labour productivity) -and the expected costs of graduating -which include the direct and indirect costs of education (tuition fees, increased living costs etc.)…”
Section: Demand For Tertiary Educationmentioning
confidence: 99%
See 1 more Smart Citation
“…It should be noted, however, that numerical simulations provided in Oliveira Martins et al (2007) show that observed differences in average returns across countries cannot be attributed to differences in returns across education fields. G e r m a n y D e n m a r k B e l g i u m H u n g a r y F i n l a n d S w e d e n A u s t r i a P o l a n d I t a l y N e t h e r l a n d s F r a n c e L u x e m b o u r g G r e e c e U n i t e d K i n g d o m C a n a d a U n i t e d S t a t e s A u s t r a l i a S w i t z e r l a n d S p a i n P o r t u g a l I r e l a n d…”
Section: Cross-country Differences In the Internal Rates Of Return Tomentioning
confidence: 97%
“…Take-up rates represent the number of aid recipients over the total number of students entitled to receive grants or loans. This attempt to compare total student costs (tuition fees and cost of living) of higher education with the available financing sources is displayed in Table 4 (details about this indicator are provided in Oliveira Martins et al (2007), Annex C). Typically, the average ratio of total costs to total funding is somewhat lower in universal funding systems than in family-based systems, despite tuition fees and living costs often being relatively high.…”
Section: Slovak Republicmentioning
confidence: 99%